PENERAPAN MODEL PEMBELAJARAN RECIPROCAL TEACHING BERBASIS KOOPERATIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP FISIKA SISWA KELAS X (UPEJ Unnes Physics Education Journal, 2012)
Based on observations, student learning outcomes of physics at SMA in Semarang still need to be improved. This study aimed to determine the activity of students, the increase of students’ understanding of concepts, and effectiveness of cooperative based reciprocal teaching model to enhance X grade students’ understanding of the physics concept. The result showed that students’ understanding of concept of experiment class was 0.46, which was categorized as medium category and 0.28, in the control class which was categorized as low category. The average of cognitive of the experiment class was 74.67 and those of the the control class was 65.48. For both affective and psychomotor aspects the mark of both classes have passed the minimum passing criteria. It was concluded that the application of Cooperative-Based Reciprocal Teaching Learning is effective to be used to improve the understanding of physics concepts at X grade on the temperature and heat material. On the aspect of affective and psychomotor it was found that the experimental class students were more active than the control class.